Aging promotes an increase in mitochondrial fragmentation in astrocytes - Araujo, Ana Paula Bergamo; Vargas, Gabriele; Hayashide, Lívia de Sá; Matias, Isadora; Andrade, Cherley Borba Vieira; de Carvalho, Jorge José; Gomes, Flávia Carvalho Alcantara; Diniz, Luan Pereira (Frontiers in Cellular Neuroscience, 2024)
Introduction Brain aging involves a complex interplay of cellular and molecular changes, including metabolic alterations and the accumulation of senescent cells. These changes frequently manifest as dysregulation in glucose metabolism and mitochondrial function, leading to reduced energy production, increased oxidative stress, and mitochondrial dysfunction—key contributors to age-related neurodegenerative diseases. Methods We conducted experiments on two models: young (3–4 months) and aged (over 18 months) mice, as well as cultures of senescent and control mouse astrocytes. Mitochondrial content and biogenesis were analyzed in astrocytes and neurons from aged and young animals. Cultured senescent astrocytes were examined for mitochondrial membrane potential and fragmentation. Quantitative PCR (qPCR) and immunocytochemistry were used to measure fusion- and fission-related protein levels. Additionally, transmission electron microscopy provided morphological data on mitochondria. Results Astrocytes and neurons from aged animals showed a significant reduction in mitochondrial content and a decrease in mitochondrial biogenesis. Senescent astrocytes in culture exhibited lower mitochondrial membrane potential and increased mitochondrial fragmentation. qPCR and immunocytochemistry analyses revealed a 68% increase in fusion-related proteins (mitofusin 1 and 2) and a 10-fold rise in DRP1, a key regulator of mitochondrial fission. Transmission electron microscopy showed reduced perimeter, area, and length-to-diameter ratio of mitochondria in astrocytes from aged mice, supported by elevated DRP1 phosphorylation in astrocytes of the cerebral cortex. Discussion Our findings provide novel evidence of increased mitochondrial fragmentation in astrocytes from aged animals. This study sheds light on mechanisms of astrocytic metabolic dysfunction and mitochondrial dysregulation in brain aging, highlighting mitochondrial fragmentation as a potential target for therapeutic interventions in age-related neurodegenerative diseases.